Diseño, construcción y puesta en marcha de un banco didáctico del sistema de frenos de estacionamiento automático para la facultad de ingeniería mecánica de la Universidad Antonio Nariño Sede Neiva (2015)
With the implementation of the didactic bank of the automatic system of stop brakes it will be possible experience the functioning of the drum brake and disc, check the hydraulic system and analyze the aspects to automate mechanical systems for one in the industry.